Challenges Encountered by Community Colleges at Shaqra University in Saudi Arabia: A Documentary Analysis - Alabdulamenem, Fahad (IIUM Journal of Educational Studies, 2016)
The principal aim of this study is to investigate to what extent the four community colleges operating under the jurisdiction of Shaqra University: Shaqra, Adduwadimi, Huraymila, and Alquwayiyah, meet the needs of Saudi Arabian society. The research method was a qualitative documentary analysis, which involved examining and interpreting official documents. The following are the primary findings of the study:(a) enrollments at the four colleges have fluctuated over the past 3 years (2012-2014); (b) the number of graduates from the four community colleges has steadily decreased, resulting in an abnormally low graduation rate overall; (c) the faculty to student ratios at the community colleges are typically small; and (d) there was a policy of continuous hiring of additional administrators and technicians between 2012 and 2014, with the result that the ratio of administrators and technicians to enrollees has become bloated. Consequently, the continued existence of these community colleges hangs-in-the-balance, and the concerned authorities need to seek urgent resolution to this problem to avoid huge financial losses and wastage on the part of the government. To resolve the on-going problems, the researcher recommends that the four community colleges at Shaqra University be just combined into two, and if necessity requires, retrenchment of faculty and administrators is conducted to achieve the ideal faculty to student ratio and administrator to student ratio. Finally, the researcher concludes that the best model for a community college system that can be adapted to the context of the Kingdom of Saudi Arabia is the American system of community colleges.